A case of coccidiosis in piglets - ΚΥΡΙΑΚΗΣ, ΣΠ.; ΑΝΔΡΕΩΤΗΣ, ΙΩ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The authors describe an outbreak of coccidiosis among piglets on a commercial pig farm in Central Greece. After reviewing the current situation of the disease, they empasize the importance of fecal examination as an aid in diagnosis, discuss the recommended treatment, the prophylaxis and hygienic measures taken. They also suggest the need for an investigation concerning the possible economic consequences of the disease on the cost of pig production on the Greek commercial pig farms.